Economics : private markets and public choice - EKELUND, Robert B (Addison-Wesly Pub, 1900)
Maximizing happiness means more than maximizing wealth, and yet many students assume economists only care about "the bottom line." "Economics: Private Markets and Public Choice emphasizes that economics is, at its base, about our society's well-being and our individual happiness in "all forms, not just profit. The authors teach students to apply economic concepts not only to key policy decisions like taxes, inflation, and free trade, but also to personal decisions such as household finance, marriage, and career choices.The Seventh Edition is enhanced by MyEconLab, the online homework system featuring automatically graded graphing problems and proven tutorial tools. Access to MyEconLab comes with every new textbook at no additional cost to the student.